MEKANISME KERJA SAMA LUAR NEGERI OLEH PEMERINTAH DAERAH - Evi Oktarina; Putri Sari Nilam Cayo (Justici, 2019)
The mechanism of foreign cooperation by the Regional Government in cooperation in economic, social culture, and other forms of cooperation, namely economic cooperation and social cultural cooperation carried out by the region with foreign parties, including border cooperation by the Regional Government (Province / District / City) bordering the territory of a foreign country. However, this does not apply to fields covered by the Joint Commission. Bilateral Consultation Forum (Bilateral Consultations), Joint Border Committee and Integrated Promotion and Sub-Regional Economic Cooperation (KESR).